Study on Basic Requirements and Critical Success Factors (CSFs) of Implementing Availability Payment in Public-Private Partnership in Regency/Municipal Government: A Case Study of Public Street Lighting in Bandung Municipal and Madiun Regency - Alia Zata Izzati Shodiqi; Rizal Z. Tamin; Iris Mahani (Journal of the Civil Engineering Forum, 2024)
Referring to PPP Books 2017-2023 issued by The Ministry of National Development Planning of Indonesia, there is only 1 out of 16 AP PPP projects at the municipal/regency level that have successfully reached the operational stage (6% success rate), i.e. Madiun Regency Public Street Lighting. Several municipal/regency AP PPP projects have failed, for example, Bandung Municipal Public Street Lighting. The widespread failures indicate that the application of AP in regional infrastructure has so far not been successful in Indonesia. This paper aims to identify the basic requirements, critical success factors, and lessons learned from AP PPP implementation in Municipal/Regency Governments. Thus, it is hoped that the future provision of regional infrastructure with the AP scheme can proceed seamlessly. This study used a mixed-method approach that combines qualitative and quantitative data from literature reviews, questionnaires, and interviews. The results showed that the basic requirements for AP PPP include the existence of regulations and institutions. The five main success factors of AP PPP in the Municipal/Regency Government are (1) a well-organized and committed public agency; (2) political support; (3) favorable and efficient legal framework; (4) stable political and economic situation; and (5) public and private sector commitments and responsibilities. The lesson learned from the case study is that fiscal capacity is not the main factor in the success of PPP in Madiun Regency, but rather the willingness of the local government to implement PPP by regularly holding capacity building and maintaining good relationships and communication with each stakeholder involved.